Lethal and severe violence: Characterizing Swedish female offenders with and without a severe mental disorder - Trägårdh, Karin; Hildebrand Karlén, Malin; Andiné, Peter; Nilsson, Thomas (Frontiers in Psychiatry, 2023)
Aim In studies on lethal and severe violence, male offenders have historically been in focus while female offenders, in comparison, have often been excluded. In this study, we aimed to characterize female violent offenders and compared those with and without a severe mental disorder (SMD). Method All females charged with lethal or attempted lethal violence, who had undergone forensic psychiatric investigations (FPI) in Sweden between 2000 and 2014, constituting the two groups SMD (n = 84) and no SMD (n = 91), were included. Information from their FPI reports and court verdicts was collected regarding background and demographics, mental health, substance use, and crime characteristics. Results Overall, both groups were often unemployed, previously victimized within close relations, had psychiatric health issues, and more than half of them had previously attempted suicide. Specifically, the SMD group more often had psychotic disorders, had attempted homicide-suicide (at the time of the crime), and had children or friends/acquaintances as victims. The no-SMD group more often manifested patterns of anxiety, personality disorders, and substance use disorders compared to the SMD group. The no-SMD group also differed from the SMD group by more often having a previous criminal record, being charged with lethal index violence, having male adult intimate partners/ex-intimate partners as victims who had abused the offender, and both offender and victim had more often been under the influence of a substance. Conclusion Female offenders of lethal and severe violence had a high prevalence of previous violent victimization which should be considered in forensic assessment and treatment regardless of the offender’s SMD status. However, more focus on substance use disorders and intimate partner relations appears relevant for females without an SMD. Contrary to that, early interventions regarding psychotic processes are probably a helpful preventive measure for females with an SMD. In sum, the heterogeneity of female offenders of lethal and severe violence emphasizes the necessity of developing nuanced interventions to meet their rehabilitative needs as well as the requirements of community protection.